PS 17-62 AORTIC ROOT DIAMETERS AND AORTIC REGURGITATIONS IN HYPERTENSIVE PATIENTS COMPARE TO A CONTROL GROUP OF NORMAL SUBJECTS. (September 2016) - Vriz, Olga; Favretto, Serena; Mos, Lucio; Palatini, Paolo; Pirisi, Mario; Bossone, Eduardo
Abstract : Objective: Aortic dimensions are realated to body size and increase with age. The association between aortic root diameters, aortic regurgitation and hypertension (HT) is disputed. Moreover there is a lack of understanding of the underlying mehanisms leading to aortic insufficiency in HT . We investigate the relationship between aortic root diameters and aortic regurgitation in newly diagnosed and never treated hypertensive patients. Design and method: Participants were 175 hypertensives (42 F and 133 M) and 302 normotensives (134 F, 168 M) age match (mean age 52.4 ± 13 vs 52.6 ± 15.2 years). Antropometric, office blood pressure (BP) measurements and a comprehensive echocardiography were performed. Aortic measures for annulus, sinuses of Valsalva, sinotubular junction and ascending aorta were taken in late diastole according to the leading edge method. The sinotubular junction/annulus ratio was calculated. Results: Hypertensive patients had significantly higher body surface area (BSA), systolic pressure (PAS), diastolic pressure (PAD), mean arterial pressure (MAP), pulse pressure (PP) (p = 0.000) than normotensives. Annulus and sinotubular junction diameters, indexed by BSA and after adjustment for gender, MAP, heart rate (HR), were significantly higher in normotensives than hypertensives. Considering subjects with aortic regurgitation (trivial or mild) we found a higher prevalence in hypertensives (25.7 % vs 10.2%, p < 0.0001). Moreover in hypertensives we found no difference in aortic diameters between patients with or without aortic regurgitation but ascending aorta /BSA (p = 0.002) whereas in healthy subjects aortic regurgitation was associated with larger aortic root diameters included sinotubular junction/annulus ratio. Conclusions: Hypertensive patients had smaller indexed aortic root dimension than normal subjects but they had heigher prevalence of trivial-mild aortic regurgitation that was not related to aortic root diameters while normotensives with aortic regurgitation had larger aortic diameters. This could be explained by the different mechanisms leading to aortic insufficiency: increased afterload in hypertensives and a trivial sinotubular/anunulus mismatch in normotensives.